Antifungal Susceptibility and Biofilm Production of Candida spp. Isolated from Clinical Samples - Munmun B. Marak; Biranthabail Dhanashree (International Journal of Microbiology)
Objective. The study aims to speciate clinical Candida isolates and detect their biofilm-forming ability and antifungal resistance. Methods. All the Candida spp. isolated from different clinical samples like pus, urine, blood, and body fluid were included in the study. Biofilm production was tested by the microtiter plate method. Antifungal susceptibility was studied by the disk diffusion method. Patient’s demographic details such as age, sex, and clinical information were collected. Presence of other risk factors such as diabetes mellitus, history of antibiotic use, and any urinary tract instrumentations was also recorded. Results. Among 90 Candida species isolated, most predominant species was found to be C. albicans (45.5%) followed by C. tropicalis (28.88%), C. krusei (20%), C. glabrata (3.33%), and C. parapsilosis (2.22%). Candida spp. were isolated from urine (43%), BAL/sputum (18.88%), high vaginal swab (8.88%), suction tips (7.77%), blood and wound swabs (6.66%), pus (3.33%), bile aspirate (2.22%), and deep tissue (1.11%). A larger number of females were affected than males, and the age group of 51 to 60 years was more susceptible to candidiasis. A higher number of C. albicans isolates produced biofilm followed by C. parapsilosis, C. tropicalis, and C. krusei. However, C. glabrata showed no biofilm production in our study. All Candida isolates were 100% sensitive to amphotericin B. Voriconazole was the next effective drug with 81.11% susceptibility. 24.44% of strains were resistant to fluconazole. Conclusion. Speciation of Candida isolates, detection of ability to form the biofilm, and monitoring of antifungal susceptibility testing are necessary for appropriate treatment.